ANALISIS PENILAIAN TINGKAT KESEHATAN PERBANKAN BUMN DAN BUSN YANG TERDAFTAR DI BEI DENGAN MENGGUNAKAN METODE CAMEL PERIODE 2014-2017 - Adinda Putri Mayangsari (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2019)
This study aims to assess the soundness of the banking industry, namely state-owned commercial banks (BUMN) and national private commercial banks (BUSN), which include assessments of capital, asset quality, management, profitability and liquidity. This research used descriptive method. The research sample taken from 4 banking companies consisting of 2 state-owned banks and 2 BUSN banks listed on the Indonesia Stock Exchange in the 2014-2017 period. Data was collected by literature review and documentation techniques. Data analysis using the CAMEL method consisting of 5 components, namely capital aspects using CAR (Capital Adequecy Ratio) ratio, earning asset quality aspects using KAP ratio (Earning Asset Quality), Management aspects using NPM (Net Profit Margin) ratio, Profitability aspect using the ROA (Return On Assets) ratio and BOPO (Operating Expenses to Operating Income), and the liquidity aspect using the LDR (Loan to Deposit Ratio) ratio. The results showed that state-owned banks (BRI and Bank Mandiri) received healthy titles during the study period (2014-2017). Meanwhile BUSN banks as well as BCA received a healthy rating every year during the study period. While CIMB Niaga Bank . received a healthy rating in 2014 and 2017, but in 20115-2016 it only received a fairly healthy rating.